The Influence of Teacher Teaching Styles on English Learning Motivation of Eighth-Grade Students at SMP Negeri 1 Afulu - Firman Setia Zalukhu; Adieli Laoli; Elwin Piarawan Zebua; Hidayati Daeli (Raja Zulkarnain Education Foundation, 2026)
This study aims to examine the relationship between teachers' teaching styles and students' learning motivation in English learning. The study was conducted at SMP Negeri 1 Afulu in the 2025/2026 academic year. This study employed a quantitative research approach with a survey design to examine the relationship between teachers' teaching styles and students' learning motivation in English learning. A quantitative approach was chosen because the data were obtained in numerical form through questionnaires and aimed to examine the relationship between variables using statistical procedures. The study population was all 112 eighth-grade students, while the study sample consisted of one eighth-grade class with 28 students and was selected using a cluster sampling technique. The research instrument was a questionnaire consisting of 25 items to measure teachers' teaching styles and 25 items to measure students' English learning motivation using a four-level Likert scale. Data were analyzed using descriptive statistics and inferential statistics with the help of IBM SPSS Statistics 25 and Microsoft Excel. Inferential analysis used rank-order correlation (Spearman) to determine the relationship between the two variables. The results of the study showed a strong positive relationship between teacher teaching style and student learning motivation, with a correlation coefficient of 0.886 and a significance level of 0.000. This finding indicates that students who have a positive perception of their teacher's teaching style tend to demonstrate higher English learning motivation. Therefore, it can be concluded that teacher teaching style is closely related to student learning motivation in English learning.